2001
DOI: 10.1177/030089160108700318
|View full text |Cite
|
Sign up to set email alerts
|

Parachordoma: A Case Report

Abstract: Parachordoma is a very rare soft tissue tumor with histological features similar to chordoma and chondrosarcoma. It should be distinguished from metastatic chordoma and extraskeletal myxoid chondrosarcoma because of its different treatment and prognosis. In this paper we report one case of parachordoma in a 20-year-old female patient. The tumor occurred in the subcutaneous tissue of the left hand as a painless, fixed, slow-growing mass. Pathologic analysis revealed a tumor composed of lobules of cells with var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…The term parachordoma was coined by Dabska 26 years later, 2 when she described in detail the features of 10 cases (including the five cases reported by Laskowski). Since this time less than 40 cases have been reported, about half of which have included details of immunohistochemistry 2–23 . The reported tumors have been nearly twice as common in men than women and the ages of those affected ranged from 4 to 86 years (mean, 32 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term parachordoma was coined by Dabska 26 years later, 2 when she described in detail the features of 10 cases (including the five cases reported by Laskowski). Since this time less than 40 cases have been reported, about half of which have included details of immunohistochemistry 2–23 . The reported tumors have been nearly twice as common in men than women and the ages of those affected ranged from 4 to 86 years (mean, 32 years).…”
Section: Discussionmentioning
confidence: 99%
“…Rarely, tumors with a similar morphology might involve peripheral sites and such tumors may cause difficulties in the diagnosis. While their most frequent designation is parachordoma, such tumors have also been described under a variety of names, all of which imply a similarity to chordoma 2–23 . Recently, however, Nielsen and colleagues suggested that rather than representing one tumor, there are two distinct chordoma‐like tumors of the periphery: chordoma periphericum and parachordoma 15 .…”
mentioning
confidence: 99%
“…The nuclei of the neoplastic cells are hyperchromatic with inconspicuous nucleoli, surrounded by clear, vacuolated, or eosinophilic cytoplasm. 28,32 As with the conventional chondrosarcoma, immunohistochemistry is helpful in most cases. Extraskeletal myxoid chondrosarcoma is positive for vimentin and S-100 protein but is usually negative for cytokeratins.…”
Section: Discussionmentioning
confidence: 99%
“…Komparativni primjerak nađen je na lokalitetu Asserie i datira se u II stoljeće. 310 U poseban tip spadaju i tri primjerka bocebalzamarija (Tab. 26, 4 i 5 i Tab.…”
Section: Staklounclassified